Synthesis, structure and redox properties of an unexpected trinuclear copper(II) complex with aspartame: [Cu(apm)(2)Cu(mu-N,O : O '-apm)(2)(H2O)Cu(apm)(2)(H2O)]center dot 5H(2)O - Cavicchioli, M.; Massabni, Antonio Carlos [UNESP]; Ferreira, AMD; Castellano, E. E.; Crespi, Marisa Spirandeli [UNESP] (Elsevier B.V., 2005)
Structural, magnetic and spectroscopic data of a new trinuclear copper(II) complex with the ligand aspartame (apm) are described. [Cu(apm)(2)CU(mu-N,O:O'-apm)(2)(H2O)Cu(apm)(2)(H2O)]-5H(2)O crystallizes in the triclinic system, space group P1 (#1) with a = 7.3300(1) angstrom, b = 15.6840(1) angstrom, c = 21.5280(1) angstrom, alpha = 93.02(1)degrees, beta = 93.21 (1)degrees, gamma = 92.66(1)degrees and Z = 1. Aspartame coordinates to Cu(II) through the carboxylate and beta-amino groups. The carboxylate groups of the two central ligands act as bidentate bridges in a syn-anti conformation while the carboxylate groups of the four peripheral ligands are monodentate in a syn conformation. The central copper ion is in a distorted square pyramidal geometry with the apical position being occupied by one oxygen atom of the water molecule. The two terminal copper(II) atoms are coordinated to the ligands in the same position but their coordination sphere differs from each other due to the fact that one copper atom has a water molecule in an apical position leading to an octahedral coordination sphere while the other copper atom is exclusively coordinated to aspartame ligands forming a distorted square pyramidal coordination sphere. Thermal analysis is consistent with the X-ray structure. EPR spectra and CV curves indicate a rupture of the trinuclear framework when this complex is dissolved in ethanol or DMF, forming a mononuclear species, with a tetragonal structure. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: copper complex; aspartame; X-ray crystal structure; EPR; cyclic voltammetry